Heterochromatic banding pattern in two Brazilian populations of Aedes aegypti - De Sousa, Rita de Cássia [UNESP]; De Campos Bicudo, Hermione Elly Melara [UNESP] (Springer Nature, 1999)
We analysed samples of Aedes aegypti from Sao Jose do Rio Preto and Franca (Brazil) by C-banding and Ag-banding staining techniques. C-banding pattern of Ae. aegypti from Sao Jose do Rio Preto examined in metaphase cells differed from Franca. The chromosomes 2, 3 and X showed centromeric C-bands in both populations, but a slightly stained centromeric band in the Y chromosome was observed only in Sao Jose do Rio Preto. In addition, the X chromosome in both populations and the Y chromosome of all individuals from Sao Jose do Rio Preto showed an intercalary band on one of the arms that was absent in Franca. An intercalary, new band, lying on the secondary constriction of chromosome 3 was also present in mosquitoes of both populations. The comparison of the present data with data in the literature for Ae. aegypti from other regions of the world showed that they differ as to the banding pattern of sex chromosomes and the now described intercalary band in chromosome 3. The observations suggested that the heterochromatic regions of all chromosomes are associated to constitute a single C-banded body in interphase cells. Ag-banding technique stained the centromeric regions of all chromosomes (including the Y) and the intercalary C-band region of the X chromosome in both populations. As Ae. aegypti populations are widespread in a great part of the world, the banding pattern variations indicate environmental interactions and may reveal both the chromosome evolutionary patterns in this species and the variations that may interfere with its vector activity.
Keywords: Aedes aegypti; C-banding; Chromosomes; Aedes; animal; brain; Brazil; chromosome banding pattern; comparative study; female; genetics; heterochromatin; interphase; male; metaphase; ovary; physiology; population genetics; testis; X chromosome; Y chromosome; Animals; Brain; Chromosome Banding; Female; Genetics, Population; Heterochromatin; Interphase; Male; Metaphase; Ovary; Testis; X Chromosome; Y Chromosome